Synthesis of Citronellol-Derived Antibacterial Polymers and Effect of Thioether, Sulfoxide, Sulfone, and Ether Functional Groups on Their Bactericidal Activity - Yook, Jinsol; Jeong, Daun; Lee, Jong-Chan (American Chemical Society, 2023)
Citronellol-derived methacrylate polymers with four side chain interconnecting groups of different polarities (PCHMXs) are synthesized to prepare bio-based bactericidal polymers. The PCHM-X bactericidal activities are significantly affected by the different functional groups determining the interaction between the polymer chain and bacterial membrane that disrupts the membrane integrity causing cytoplasmic leakage, the main contributor to the polymer antibacterial properties. PCHM-SO, with a large dipole moment and strong hydrogen bonding ability, shows the best bactericidal activity among PCHM-Xs due to the strongest interactions with the bacterial membrane components. A sulfoxide-group-containing polymer with excellent bactericidal activity (99.99%) and the systematic study of the effect of different functional groups on the bactericidal activity are first reported herein.